Recoverable Autonomous Sonde for subglacial lakes exploration: heating control system design. Issue 85 (29th September 2021) - Yu, Haibin; Zhu, Tianxin; Jiang, Xiao; Tang, Yongzhen; Li, Xiaodong; Li, Chong; Huang, Shengmiao; Shi, Jianguang; Sun, Youhong; Talalay, Pavel; Fan, Xiaopeng; Li, Xiao; et al.
Abstract: Drilling and sampling are the most direct and effective methods available to study Antarctic subglacial lakes. Based on the Philberth probe, a Recoverable Autonomous Sonde (RECAS) allows for in situ lake water measurement and sampling, through the addition of an upper thermal tip and a cable recoiling mechanism. RECAS-200, a prototype of RECAS, has a drilling depth of 200 m, a surface supply voltage of 800 VAC and a downhole power of ~9.6 kW during drilling. In this study, a heating control system for RECAS-200 was designed. The system avoids the need for high-power step-down converters, by separating heating power from control power, thereby reducing the overall weight of the probe and avoiding the need to increase cable diameter. We also introduce a self-developed, small, solid-state, 800 VAC power regulator and a fuzzy PID temperature control algorithm. Their purpose was to manage the power adjustment of each heating element and to provide closed-loop temperature control of certain heating elements which can easily burn out due to overheating. Test results indicated that the proposed RECAS-200 heating control system met all our design specifications and could be easily assembled into the RECAS-200 probe.